2022
DOI: 10.1155/2022/5469795
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targets of Bufalin on Renal Carcinoma and Mechanisms: Experimental Validation of Network Pharmacology Analysis

Abstract: The possible targets underlying the activity of bufalin on renal cell carcinoma (RCC) were investigated using network pharmacology and experimental approaches. PharmMapper and other databases were explored for predicting the bufalin targets and RCC-related targets. Finally, the enriched pathways and the targets were analyzed by the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) pathway enrichment analyses. Furthermore, in vitro cell experiments were used to verify bufalin activation of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The protein concentrations were determined using a bicinchoninic acid (BCA) assay kit (Bio-Rad Laboratories, Inc., Hercules, CA, USA). Equal amounts (20–25 µg) of protein lysate were then resolved on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), transferred to polyvinylidene fluoride (PVDF) membranes (Millipore, Burlington, MA, USA), and immunoblotted as formerly described ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentrations were determined using a bicinchoninic acid (BCA) assay kit (Bio-Rad Laboratories, Inc., Hercules, CA, USA). Equal amounts (20–25 µg) of protein lysate were then resolved on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), transferred to polyvinylidene fluoride (PVDF) membranes (Millipore, Burlington, MA, USA), and immunoblotted as formerly described ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Its structure is similar to digitalis toxin (10)(11)(12). Some studies have demonstrated that bufalin exerts significant anti-tumor activity by inhibiting cell proliferation and angiogenesis and inducing programmed cell death (13)(14)(15). More recently, studies have discovered that bufalin can inhibit the invasion and metastasis of hepatocellular carcinoma by regulating the PI3K/Akt/Mtor/HIF-1α axis (16,17).…”
Section: Original Articlementioning
confidence: 99%